Hypoglycaemic activity of petai papan (Parkia speciosa, Hassk) - Jamaluddin, Fathaiya; Mohamed, Suhaila (1990)
The administration of the chloroform extract of P. speciosa to alloxan diabetic rats produced a significant decrease in blood glucose levels. The hypoglycaemic response is approximately proportional to the square root of the close given. The antidiabetic activity is maximum after 4-5 hrs after oral treatment, and lasted for more than 24 hrs.